Innovation and Sustainability: The Story of Indian QSR Foodbox (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2020)
Sustainopreneurship is a neologism created by merging the words sustainability and entrepreneurship. Today as the world is moving towards the fourth industrial revolution it has now become imperative for businesses to come up with new ideas which can sustain in future. The economy also values such people who can turn our day to day concerns into business opportunities. So was the intent of Mr Satish Chamyvelumani, Founder of Foodbox: “The idea was to serve people with food from their favourite brands while on the move.” In recent years, there have been great strides in the field of food technology. One such stride was made by Satish Chamyvelumani, who is a pioneer in a complete “Indian” Quick Service Restaurant sector. The global market research organization CRISIL states that the Indian QSR is largely dominated by international players (>65%).The reason lies in their western menu which has high shelf life, is compatible with the cold storage set-up, prepared with few ingredients and goes well with quick to serve menu. The present case is about an out and out Indian player in QSR sector Foodbox now known as Frshly. It not only defies the set pattern of international brands but also keeps itself ahead of them by opting innovation in food retail. It has made a significant entry through its speed, hygiene, packaging and above all the Indian-ness of its menu in this format, which until now is first of its kind. There is also a contrast in the target segment, where the international brands go for casual dining category; it takes care of the utility segment-the working class which requires it as a second option to home-made food in form of lunch/dinner. It is also not an app based model which we generally find in food tech business rather it is more on the ground model. The innovation comes in the form of the dispenser which dishes out food within 90 seconds fresh and hot!
Keywords: QSR; Innovation; Automated Food Dispenser; World Class Packaging; Multiple Restaurants and Sustainability